Effects of interest rate on underpricing of US IPOs - Lim, Eric Cheng How (2008)
This paper investigates the relationship between market-wide interest rate, using U.S 30-day Commercial Paper rate as a proxy, and the uderpricing of U.S IPOs issued between 1985-2003.